Kamisama kiss. Vol. 12 - Suzuki, Julietta (Viz Media, 2013)
"Himemiko, ayakashi ruler of Tatara swamp, is happily dating her human sweetie Kotaro. But yokai/human relationships are hard to manage, especially when the human has no idea who he's dating! When the supernatural starts to intrude, can Himemiko tell Kotaro the truth about herself? Or will she lose him no matter what she does?"--Page 4 of cover.